Individual Factors of Botulinum Type A in Treatment of Gummy Smile: A Prospective Study. (15th December 2020) - Gong, Xi; Huang, Hongyuan; Gu, Chenyang; Li, Facheng; Zou, Lidong; An, Yang; Han, Xuefeng; Tang, Zhihui
Abstract: Background: Botulinum type A (BTX-A) injection is a promising treatment for gummy smile (GS), although its effects are varied and inconsistent. Objectives: The aim of this study was to explore the effect of individual factors on BTX-A treatment for GS, and to establish treatment expectations. Methods: In this prospective clinical study, a standardized technique comprising bilateral single-point injections of 2 U BTX-A (total, 4 U) was administered to all GS patients. Data were collected at baseline and after 4, 12, and 32 weeks of follow-up. Twenty-nine potential individual factors were analyzed by correlation and regression analysis to exclude confounding bias. Results: Ninety-four patients completed the BTX-A treatment. After adjusting for potential confounding factors, the correlation and regression analysis confirmed the following formula: anterior gingival exposure (GE) at 4 weeks = 1.44 + (0.94 × baseline anterior GE) − (1.88 × sex) (where male = 1 and female = 2). The confidence interval (CI) of the prediction showed that for all female participants with baseline anterior GE <5.3 mm, the 95% CI of anterior GE was 0.3 to 3.0 mm after 4 weeks of treatment, and 3.0 to 8.9 mm with baseline anterior GE ≥6 mm. For male patients with baseline anterior GEs of 3 and ≥4.6 mm, the 95% CIs were 1.5 to 3.3 mm and 3.2 to 8.9 mm, respectively. Conclusions: The effect of average-dose BTX-A treatment for GS depended on GS severity and patient's sex, rather than GS etiology and other factors. Female participants with baseline anterior GE <5.3 mm were more likely to show complete improvement after 4 weeks of treatment. However, female participants with baseline anterior GE ≥6.0 mm or male participants were less likely to show complete improvement at 4 weeks. Level of Evidence: 4: